Nature-Based Solutions in Coastal and Estuarine Areas of Europe - Moraes, Roberta P. L.; Reguero, Borja G.; Mazarrasa, Inés; Ricker, Max; Juanes, José A. (Frontiers in Environmental Science, 2022)
Momentum for sustainable and climate resilience solutions for coastal protection are growing globally given the pressing need to prevent further loss of biodiversity and ecosystems while meeting the climate change adaptation and mitigation goals. Nature-Based Solutions (NbS) represent an opportunity to align environmental and resilience goals, at a time of strained budgets in a global context and when short-term needs may run counter to long-term goals. In Europe, NbS fit the mandates of major EU environmental and climate change policies by restoring biodiversity and enhancing climate-resilience and carbon sequestration. Previous studies have compiled scientific evidence about hydro-meteorological hazards for the use of NbS. However, their implementation at scale is still lacking. As the knowledge and experience with NbS for adaptation to natural hazards and climate change increases, it becomes more important to draw lessons learned and insights for replicating and scaling up NbS, especially in coastal areas where their implementation is still limited compared to other environments. This study analyzed NbS case studies across European coastal and estuarine areas to draw key lessons, understand better the current status of implementation, and identify key challenges and gaps. From a total of 59 NbS case studies associated with flooding, erosion and biodiversity loss, results show an increase in NbS implementation since 1990s, but most rapidly between 2005 and 2015. Most of the case studies are hybrid solutions employing wetlands, predominantly located in the United Kingdom (UK) and the Netherlands. Funding of NbS is largely from public sources, and rarely come from a single or a private source. Three-quarters of the case studies reported monitoring activities, but more than half did not disclose quantitative results related to effectiveness against flooding and/or erosion. The need to improve coastal defenses was indicated as the main motivation for NbS implementation over traditional structures, while sustainability was the most mentioned additional reason. Although a variety of co-benefits and lessons learned was identified, clearer descriptions and enhanced details of such information are required. There is a need for tools and strategies to expand knowledge sharing of lessons learned to enable further replication of successful cases in other areas.